Implementasi Media Pembelajaran Visual dalam Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) di Sekolah Dasar - Elia Mushoda; Emha Dzia'ul Haq; Sri Adiningsih (The Prime, 2026)
The teaching of Natural and Social Sciences (IPAS) under the Merdeka Curriculum requires the use of instructional media capable of enhancing conceptual understanding and actively engaging students. However, in practice, IPAS instruction in elementary schools still faces challenges due to students’ limited understanding of abstract concepts. This study aims to analyze the effectiveness of using visual learning media in supporting IPAS learning and improving student learning outcomes at MIS Guppi Teppo. This study employs a qualitative approach using the Miles and Huberman data analysis model, which includes data reduction, data presentation, and drawing conclusions. Data collection techniques were conducted through observation, interviews, and documentation. The results of the study indicate that the use of visual learning media has a positive impact on students’ learning processes and outcomes. Visual media help students understand abstract concepts in a more concrete and easily comprehensible way, thereby increasing student engagement, motivation, creativity, and learning outcomes in IPAS instruction. Therefore, visual learning media need to be continuously integrated into the implementation of the Merdeka Curriculum to support the creation of effective and meaningful learning in elementary schools.